2014
DOI: 10.1080/17461391.2014.984768
|View full text |Cite
|
Sign up to set email alerts
|

The influence of playing surface on physiological and performance responses during and after soccer simulation

Abstract: The aim of this study was to investigate the effect of playing surface on physiological and performance responses during and in the 48 h after simulated soccer match play. Blood lactate, single-sprint, repeated-sprint and agility of eight amateur soccer players were assessed throughout a 90-min soccer-simulation protocol (SSP) completed on natural turf (NT) and artificial turf. Counter-movement jump, multiple-rebound jump, sprint (10 m, 60 m), L-agility run (L-AR), creatine kinase (CK) and perception of muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 41 publications
8
28
1
Order By: Relevance
“…During competitive games, Andersson et al 10 observed similar running (e.g., sprint number, high-intensity running and total covered distance) and technical (e.g., standing tackles) patterns on AT compared to NG. Moreover, single sprint performance, 11 as well as jumping and agility performances 12,13 appear to be similar on AT and NG during a soccer-simulation protocol. On the other hand, the effect of playing surface on repeated sprint ability (RSA), on the other hand is equivocal.…”
Section: Introductionmentioning
confidence: 81%
“…During competitive games, Andersson et al 10 observed similar running (e.g., sprint number, high-intensity running and total covered distance) and technical (e.g., standing tackles) patterns on AT compared to NG. Moreover, single sprint performance, 11 as well as jumping and agility performances 12,13 appear to be similar on AT and NG during a soccer-simulation protocol. On the other hand, the effect of playing surface on repeated sprint ability (RSA), on the other hand is equivocal.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, there is an acute effect on the isometric strength of the associated hamstrings during knee flexion [39], a basic movement in jump technique. This post-match fatigue remains significant 24 hours post-match for this test [7], and in most cases there is no functional recovery until the 72 hours post-match [35,38]. However, Stone et al [35] found no significant differences in this decline in their study.…”
Section: Discussionmentioning
confidence: 78%
“…This post-match fatigue remains significant 24 hours post-match for this test [7], and in most cases there is no functional recovery until the 72 hours post-match [35,38]. However, Stone et al [35] found no significant differences in this decline in their study. It should be noted that age could also be a factor in this test, because although the effect of fatigue has been elucidated in young players [40].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations